Age, Sex, and BMI Influence on Copper, Zinc, and Their Major Serum Carrier Proteins in a Large European Population Including Nonagenarian Offspring From MARK-AGE Study. (13th May 2021) - Piacenza, Francesco; Giacconi, Robertina; Costarelli, Laura; Basso, Andrea; Bürkle, Alexander; Moreno-Villanueva, María; Dollé, Martijn E T; Jansen, Eugène; Grune, Tilman; Weber, Daniela; Stuetz, Wolfgang; Gonos, Efstathios S; et al.
Abstract: The analysis of copper (Cu) and zinc (Zn) along with their major serum carriers, albumin (Alb) and ceruloplasmin (Cp), could provide information on the capacity of humans to maintain homeostasis of metals (metallostasis). However, their relationship with aging, sex, body mass index, as well as with nutritional and inflammatory markers was never investigated in a large-scale study. Here, we report results from the European large-scale cross-sectional study MARK-AGE in which Cu, Zn, Alb, Cp, as well as nutritional and inflammatory parameters were determined in 2424 age-stratified participants (35–75 years), including the general population (RASIG), nonagenarian offspring (GO), a well-studied genetic model of longevity, and spouses of GO (SGO). In RASIG, Cu to Zn ratio and Cp to Alb ratio were higher in women than in men. Both ratios increased with aging because Cu and Cp increased and Alb and Zn decreased. Cu, Zn, Alb, and Cp were found associated with several inflammatory as well as nutritional biomarkers. GO showed higher Zn levels and higher Zn to Alb ratio compared to RASIG, but we did not observe significant differences with SGO, likely as a consequence of the low sample size of SGO and the shared environment. Our results show that aging, sex, body mass index, and GO status are characterized by different levels of Cu, Zn, and their serum carrier proteins. These data and their relationship with inflammatory biomarkers support the concept that loss of metallostasis is a characteristic of inflammaging.